PENDAMPINGAN SISTEM INFORMASI BARANG BERBASIS WEB UD. ASAFA JAMUR TIRAM - Muflihah, Nur; Ayu N.F.A, Fatma; Mayasari, Andhika; Sumarsono, Sumarsono; Minto, Minto; Yulianto, Totok; Rahmawan, Sulung (ABIDUMASY, 2024)
The community service program (PKM) was carried out at UD. Asafa Jamur Tiram which is a business group that produces fresh mushrooms and provides baglog growing media. Based on the results of discussions with partners, there are problems faced related to the goods information system which has been recorded manually. Business development demands that information is faster and more precise so that an efficient planning system is needed in managing and recording inventory of materials, stock of goods, finished products and information on the entry and exit of goods. Therefore, in the community service program, a web-based goods information system has been introduced which allows a centralized database and can be accessed anywhere. The implementation of PKM is carried out by first coordinating with partners to find the problems faced then planning the PKM activity program. Furthermore, compiling a guide to mentoring material, then implementing mentoring activities, and evaluating the results of the implementation of mentoring. As a result of this mentoring program, the partners were satisfied and the application of the web application could improve the management of goods and sales due to the sharing of inventory information from the central management to the lower level.